Synthesis of α-Thiooximes by Addition of Thiols to N,N-Bis(oxy)-enamines: A Comparative Study of S-, N-, and O-Nucleophiles in Michael Reaction with Nitrosoalkene Species - Naumovich, Yana A.; Kokuev, Aleksandr O.; Sukhorukov, Alexey Yu.; Ioffe, Sema L. (Synlett, 2018)
Nucleophilic addition of thiols to N,N-bis(oxy)enamines (nitrosoalkene acetals) produce valuable α-thiooximes in a highly efficient manner. The reaction was found to be solvent-dependent, likely because of distinct mechanisms operating in nonpolar and basic solvents (involving either Brønsted acid or Lewis base catalysis). By performing a series of competition experiments, the relative reactivity of S-, N-, and O-nucleophiles in reaction with N,N-bis(oxy)enamines was determined for the first time. Interestingly, the relative nucleophilicity was found to be highly dependent on the solvent, which allows regioselective control of these reactions by using an appropriate medium.
Keywords: thiols; nitrosoalkenes; oximes; Michael addition; solvent effects